Host Factor Predictors in Long-term Nonprogressors HIV-1 Infected with Distinct Viral Clades - dos Santos, Jucelia S.; de Almeida, Sergio Monteiro; Ferreira, Guilherme Silveira; Bordignon, Juliano; Maia Teixeira, Sylvia Lopes; Martins Lima, Alberto Cardoso; Raboni, Sonia Mara (Current HIV Research, 2017)
Background: HIV-1+ long-term nonprogressors (LTNPs) maintain natural control of viral infection. This study sought to identify and characterize HIV- LTNPs series case, regarding the presence of possible host factors that may be associated with this status. Methods: We evaluated the plasma levels of IP-10/IL-8 chemokines, HLA-B alleles, and IL28B rs12979860 polymorphism in 24 LTNPs who presented with infection by different clades of HIV-1. Results: IL-8 chemokine was significantly higher in progressors than in LTNPs, but there was no difference between the LTNP subgroups. There was a negative correlation in CD4+ T cell (TC) count and IL-8 dosage, and a positive correlation with CD8+ TC. IP-10 chemokine levels were associated with viremia, and the elite controller (EC) subgroup showed nearly the same level than healthy individuals and progressors with viral load suppressed. Furthermore, the CD4+ TC count, percentage of CD4+ TC, and CD4/CD8 ratio were negatively correlated with IP-10. No association was found in plasma levels of IL-8 and IP-10 chemokines and HIV-1 clades. In the EC/viremic controller subgroup, 80% presented with at least one HLA-B allele previously considered as potentially protective for AIDS progression. No association was observed between the HLA-B alleles and HIV- 1 clades. The IL28B CC genotype was identified in 87.5% of LTNPs. Conclusion: In this LTNP series case we observed different host factors that may be contributing to their nonprogressor status, and the association of these factors with the control of infection progression may be critically important for future therapeutic and prophylactic options in HIV-1 infection.
Keywords: HIV-LTNP